Civil servants and globalization : integrating MENA countries in a globalized economy - Verheijen, Tony, 1967- (Transnational Administration and Global Policy., 2022)
This volume analyses the impact of globalization on civil service systems across the Middle East and North Africa. It presents an analytical model to assess how globalization influences civil servants and traces the shifting patterns of power and accountability between civil servants, politicians and other actors.